Improving Student Discipline Character through Habituation of Dhuha Prayers at School in Class IV SD Negeri 017 Rambah Odd Semester Academic Year 2024/2025 - Imisuriati, Imisuriati (Indonesian Journal of Basic Education, 2024)
This class action research aims to improve the learning outcomes of grade VI students of SD Negeri 012 Tambusai in Islamic Religious Education subjects, especially on the material of wudu, through the application of the scientific approach. This research was conducted in two cycles, each of which consisted of four stages, namely planning, implementation, observation, and reflection. The research subjects were 34 students of class VI in the odd semester of the 2024/2025 academic year. Data collection techniques used learning outcome tests and observation of student and teacher activities. The results showed that the scientific approach could improve student learning outcomes from an average score of 63.2 in pre-action to 70.4 in cycle I, and increased again to 82.1 in cycle II. The percentage of learning completeness also increased from 52.94% at pre-action to 88.24% at the end of cycle II. Student and teacher activities in the learning process also showed significant improvement. Thus, the scientific approach is proven effective in improving learning outcomes and active involvement of students in wudu material.